U C Berkeley Co-op Friends 18th Annual Heavy-St. Francis Hotel - Watkins, Howard::::::::: (1986)
Kathy Muniz, Cathy Barkett, Bonnie Neary, Jerry Neary (looking at photo album), Terri Mesple, Joe Barkett